A Comparison of Fidelity Implementation Frameworks Used in the Field of Early Intervention. (June 2023) - Lemire, Colombe; Rousseau, Michel; Dionne, Carmen
Implementation fidelity is the degree of compliance with which the core elements of program or intervention practices are used as intended. The scientific literature reveals gaps in defining and assessing implementation fidelity in early intervention: lack of common definitions and conceptual framework as well as their lack of application. Through a critical review of the scientific literature, this article aims to identify information that can be used to develop a common language and guidelines for assessing implementation fidelity. An analysis of 46 theoretical and empirical papers about early intervention implementation, published between 1998 and 2018, identified four conceptual frameworks, in addition to that of Dane and Schneider. Following analysis of the conceptual frameworks, a four-component conceptualization of implementation fidelity (adherence, dosage, quality and participant responsiveness) is proposed.